IMPLEMENTASI ENTERPRISE RESOURCE PLANNING MODUL ACCOUNTING BERBASIS ODOO 16 PADA USAHA JASA SERVIS - Rohmawatik, St.; Wilasittha, Acynthia Ayu (TEMA, 2023)
This study aims to provide an implementation plan and find out how to implement an Odoo 16-based Accounting module ERP system in PT XYZ's service business. The research method used is a qualitative descriptive research method with case studies. The data used in this study consisted of two types, namely primary data obtained through an interview process and secondary data collected through a literature review. The results of this study reveal that the implementation of the ERP accounting module system can be carried out well and provides significant changes and benefits, especially in managing the company's accounting information system. Implementation of the ERP accounting module system is able to increase the efficiency and effectiveness of business process management at PT XYZ, which previously still relied on manual systems in managing its business processes, improve and increase integration between various divisions in the company so that information reception becomes more optimal, and the process of preparing financial reports is more automated and can be accessed at any time in real time.